Isolation of BVDV-1a, 1m, and 1v strains from diarrheal calf in china and identification of its genome sequence and cattle virulence - Zhu, Jie; Wang, Chen; Zhang, Lina; Zhu, Tingting; Li, Hanxiong; Wang, Yunqiu; Xue, Kaili; Qi, Mingpu; Peng, Qingjie; Chen, Yingyu; Hu, Changmin; Chen, Xi; et al. (Frontiers in Veterinary Science, 2022)
Bovine viral diarrhea virus (BVDV) is an important livestock viral pathogen responsible for significant economic losses. The emerging and novel BVDV isolates are clinically and biologically important, as there are highly antigenic diverse and pathogenic difference among BVDV genotypes. However, no study has yet compared the virulence of predominant genotype isolates (BVDV-1a, 1b, and 1m) in China and emerging genotype isolate BVDV-1v. The serological relationship among these genotypes has not yet been described. In this study, we isolated three BVDV isolates from calves with severe diarrhea, characterized as BVDV-1a, 1m, and novel 1v based on multiple genomic regions (including 5′-UTR, Npro, and E2) and phylogenetic analysis of nearly complete genomes. For the novel genotype, genetic variation analysis of the E2 protein of the BVDV-1v HB-03 strain indicates multiple amino acid mutation sites, including potential host cell binding sites and neutralizing epitopes. Recombination analysis of the BVDV-1v HB-03 strain hinted at the possible occurrence of cross-genotype (among 1m, 1o, and 1q) and cross-geographical region transmission events. To compare pathogenic characters and virulence among these BVDV-1 genotypes, newborn calves uninfected with common pathogens were infected intranasally with BVDV isolates. The calves infected with the three genotype isolates show different symptom severities (diarrhea, fever, slowing weight gain, virus shedding, leukopenia, viremia, and immune-related tissue damage). In addition, these infected calves also showed bovine respiratory disease complexes (BRDC), such as nasal discharge, coughing, abnormal breathing, and lung damage. Based on assessing different parameters, BVDV-1m HB-01 is identified as a highly virulent strain, and BVDV-1a HN-03 and BVDV-1v HB-03 are both identified as moderately virulent strains. Furthermore, the cross-neutralization test demonstrated the antigenic diversity among these Chinese genotypes (1a, 1m, and 1v). Our findings illustrated the genetic evolution characteristics of the emerging genotype and the pathogenic mechanism and antigenic diversity of different genotype strains and provided an excellent vaccine candidate strain and suitable BVDV challenge strain for the comprehensive prevention and control of BVDV.